Implementation of the Policy for the Elimination of Movable State Property at Nusa Cendana University - OTTEMUSU, Yohanis; ROSARI, Petrus D E; NURSALAM, Nursalam (Journal of Tourism Economics and Policy, 2024)
No matter how great a policy plan or program is, if it is not realized properly and correctly then the program or policy will be in vain. Policy implementation requires policy implementers who are truly honest, have appropriate competence, are highly committed to producing their goals and really pay attention to applicable government regulations.The method used in this research is a descriptive method with a qualitative approach with a total number of 33 people who were determined purposively then the primary and secondary data collected were analyzed using data analysis techniques from Creswell (2016).In this research the author uses the policy implementation model from Donald Van Meter and Carl E. Van Horn (1975) which states that there are six variables that influence the implementation of the policy of eliminating movable state property at Nusa Cendana University, namely; (1) policy standards in the form of regulations regarding the elimination of movable state property at Nusa Cendana University are unable to influence policy targets; (2). the existence of sufficient resources; (3) communication between organizations and strengthening activities is still not effective; (4) the characteristics of implementing agents have a level of communication that is not yet open; (5) supportive socio-economic and political conditions; (6) the implementor's disposition where a situation is considered very complex or controversial, so that the implementor finds it very difficult to take a firm stance on the BMN elimination policy.